2022
DOI: 10.1002/deo2.177
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of liquid‐based cytology in serial pancreatic juice aspiration cytological examination

Abstract: Objectives Serial pancreatic juice aspiration cytological examination (SPACE) via endoscopic retrograde cholangiopancreatography is a useful diagnostic method for early‐stage pancreatic cancer, such as carcinoma in situ that are difficult to diagnose by endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA). However, the diagnostic accuracy of SPACE is low, which is attributed to problems regarding specimen treatment. Hence, we evaluated the diagnostic efficacy of liquid‐based cytology (LBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 113 The method is initiated via ERCP, whereby an endoscopically placed nasopancreatic drainage allows for serial measurements of pancreatic juice for cytology, or ‘liquid biopsy’. 114 Of note, the method carries the risk of post-ERCP pancreatitis.…”
Section: Further Developments and Novel Technologymentioning
confidence: 99%
See 1 more Smart Citation
“… 113 The method is initiated via ERCP, whereby an endoscopically placed nasopancreatic drainage allows for serial measurements of pancreatic juice for cytology, or ‘liquid biopsy’. 114 Of note, the method carries the risk of post-ERCP pancreatitis.…”
Section: Further Developments and Novel Technologymentioning
confidence: 99%
“…In this setting, some investigators have used a technique called serial pancreatic juice aspiration cytologic examination (SPACE) for the diagnosis. [111][112][113][114] The approach is not universally available, and early experience comes mainly from Japan, but may represent a useful diagnostic method in select cases for early-stage pancreatic cancers, such as carcinoma in situ that are difficult to diagnose by endoscopic ultrasound-guided fine needle aspiration (EUS-FNA). 113 The method is initiated via ERCP, whereby an endoscopically placed nasopancreatic drainage allows for serial measurements of pancreatic juice for cytology, or 'liquid biopsy'.…”
Section: Pancreatic Juice and Cyst Fluidsmentioning
confidence: 99%
“…They also reported that SPACE is particularly useful for diagnosing intraepithelial carcinomas that cannot be delineated using EUS. Since then, there have been increasing reports on diagnosing intraepithelial pancreatic cancer using SPACE, mainly in Japan [ 85 88 ].…”
Section: A Diagnostic Approach For Early-stage Pdacmentioning
confidence: 99%